The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/ijerph16224556
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Vertical Trunk Inclination Angle and Pelvic Inclination as the Result of Mid-High-Heeled Footwear on Static Posture Parameters in Asymptomatic Young Adult Women

Abstract: The influence of high-heel footwear on the lumbar lordosis angle, anterior pelvic tilt, and sacral tilt are inconsistently described in the literature. This study aimed to investigate the impact of medium-height heeled footwear on the static posture parameters of homogeneous young adult standing women. Heel geometry, data acquisition process, as well as data analysis and parameter extraction stage, were controlled. Seventy-six healthy young adult women with experience in wearing high-heeled shoes were enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 94 publications
4
11
0
Order By: Relevance
“…For Case Study II, the 3D datasets considered were from the PRESIOUS project [ 28 ]. The postprocessing of the data for the proposed method was written in FRAMES, which was also developed at the Faculty of Mechatronics, Warsaw University of Technology, Poland, and written in C++ [ 29 ].…”
Section: Results and Analysismentioning
confidence: 99%
“…For Case Study II, the 3D datasets considered were from the PRESIOUS project [ 28 ]. The postprocessing of the data for the proposed method was written in FRAMES, which was also developed at the Faculty of Mechatronics, Warsaw University of Technology, Poland, and written in C++ [ 29 ].…”
Section: Results and Analysismentioning
confidence: 99%
“…Regarding pelvic inclination, the current result is supported by the previous studies of Weitkunat et al (2016) and Elsayed et al (2018), who revealed that pelvic inclination remains unchanged in high-heeled shoe users. However, Michoński et al (2019) concluded that vertical TI and pelvic inclination decreased due to mid-high-heeled shoes in young adult women. The non-significant changes in spinopelvic parameters obtained from our study may be explained because the primary compensation would occur in the lower limb in non-habitual high-heeled shoe wearers, with knee flexion compensating initially the ankle plantar flexion.…”
Section: Discussionmentioning
confidence: 96%
“…The FRAMES software package, developed at the Institute of Micromechanics and Photonics, Faculty of Mechatronics of the Warsaw University of Technology [34], was used to extract the relevant data from 4D measurement sequences.…”
Section: Discussionmentioning
confidence: 99%